Female Genital Tract Bacterial Coisolates With Candida albicans in Patients Without Clinical Vaginitis - G. R. G. Monif; H. J. Carson (Hindawi Limited, 1998)
Objective: In vitro, Candida albicans has demonstrated the ability to inhibit replication of selected bacteria. Little information exists on the impact of C. albicans on the vaginal bacterial flora in vivo. The purpose of this study is to identify the coexisting bacterial flora when C. albicans is isolated from vaginal cultures submitted to a hospital-based testing facility for reasons other than vulvovaginitis.